Perceptions of Firms Participating in a Circular Economy - Cristoni, Nicolò; Tonelli, Marcello (European Journal of Sustainable Development, 2018)
Circular Economy (CE) is today a major concept within the sustainability debate (Geissdoerfer, Savageta, Bocken & Hultinkb, 2017). Its theoretical arguments are widely accepted – especially at a cross-country institutional level – but businesses still seem reluctant to acknowledge it as a revenue-making paradigm. This ongoing study aims to reveal where, along the value chain, firms are more unaware of CE best practice and/or reluctant to invest. After a comprehensive review of sustainable business models, the authors suggest a framework for circularity in business strategy as a beginning foothold on their research agenda. Next, the authors rely on expert informants to identify the most suitable areas in the value chain for the implementation of CE actions. Finally, an online free-access survey-like tool is launched to invite firms self-assessing (1) how relevant those identified areas are for their respective industries and (2) how CE-mature they feel regarding those areas. The initial results attest low consciousness of the CE potential across industries and even lower levels of maturity, especially by SMEs. Despite the growing evidence of Sustained Competitive Advantage (SCA) achieved by pioneering companies moving away from linear forms of production, through the development of new core competencies (Prahalad & Hamel 1990), most firms still perceive CE as something not applicable to them or too costly and risky to implement. Keywords: Circular economy (CE); core competencies; grounded theory; SMEs; sustainable business models; Sustained Competitive Advantage (SCA); value chain